2019
DOI: 10.1038/s41598-019-50225-w
|View full text |Cite
|
Sign up to set email alerts
|

Potential group B Streptococcus interspecies transmission between cattle and people in Colombian dairy farms

Abstract: Group B Streptococcus (GBS), is a leading cause of neonatal death and an emerging pathogen in adults. Additionally, GBS is a bovine pathogen causing intramammary infections. The likelihood of GBS interspecies transmission is largely unknown. We explored the potential transmission of GBS between cattle and people on dairy farms in Colombia and compared the antimicrobial resistance (AMR) profiles of isolates from both host species. Across 33 farms, throat swabs and rectal swabs were collected from 191 people, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 53 publications
1
37
1
Order By: Relevance
“…S. agalactiae has been considered an extremely contagious mastitis pathogen for several years, and an important human pathogen. It was reported that some clonal complexes of S. agalactiae were shared between cows and farm personnel, indicating the zoonotic potential of this species ( Cobo-Angel et al, 2019 ). These pathogens are also producers of biofilms ( Gomes et al, 2016 ; Reinoso, 2017 ; Alves-Barroco et al, 2019 ; Horiuk et al, 2019 ), and this virulence characteristic has been associated with persistent infections and development of antibiotic resistance ( Olson et al, 2002 ; Ruppen et al, 2017 ).…”
Section: Clinical and Veterinary Relevance Of Pyogenic Biofilmmentioning
confidence: 99%
“…S. agalactiae has been considered an extremely contagious mastitis pathogen for several years, and an important human pathogen. It was reported that some clonal complexes of S. agalactiae were shared between cows and farm personnel, indicating the zoonotic potential of this species ( Cobo-Angel et al, 2019 ). These pathogens are also producers of biofilms ( Gomes et al, 2016 ; Reinoso, 2017 ; Alves-Barroco et al, 2019 ; Horiuk et al, 2019 ), and this virulence characteristic has been associated with persistent infections and development of antibiotic resistance ( Olson et al, 2002 ; Ruppen et al, 2017 ).…”
Section: Clinical and Veterinary Relevance Of Pyogenic Biofilmmentioning
confidence: 99%
“…Recently, GBS associated antimicrobial resistance has also emerged. Clindamycin‐resistant strains have caused more than 40 % of GBS infections, limiting prevention and treatment options for people with severe penicillin allergy in the US, and a human GBS ST1 isolate showed a surprisingly high penicillin resistance in Colombia …”
Section: Introductionmentioning
confidence: 99%
“…Such comparisons, however, are not necessary for evolutionary analysis, whereby host species jumps have commonly been inferred based on sequence data of isolates derived from different host species without known interactions or epidemiological relatedness [19,61,62]. For the emergence of GBS in farmed species, several routes of transmission from humans to animals can be envisaged, including, in the case of fishes, the use of human waste for nutrient recycling and, in the case of cattle, the handling and milking of cows, which may lead to direct human-to-animal transmission [6,58,41]. Changes in animal husbandry systems combined with pathogen evolution are the likely explanation for the re-emergence of GBS, which has been observed in several countries in Europe [2,18,63].…”
Section: Concluding Commentsmentioning
confidence: 99%